MtPIN1 and MtPIN3 Play Dual Roles in Regulation of Shade Avoidance Response under Different Environments in Medicago truncatula - Zhang, Xue (Int J Mol Sci, 2020)
Polar auxin transport mediated by PIN-FORMED (PIN) proteins is critical for plant growth and development. As an environmental cue, shade stimulates hypocotyls, petiole, and stem elongation by inducing auxin synthesis and asymmetric distributions, which is modulated by PIN3,4,7 in Arabidopsis. Here, we characterize the MtPIN1 and MtPIN3, which are the orthologs of PIN3,4,7, in model legume species Medicago truncatula. Under the low Red:Far-Red (R:FR) ratio light, the expression of MtPIN1 and MtPIN3 is induced, and shadeavoidance response is disrupted in mtpin1 mtpin3 double mutant, indicating that MtPIN1 and MtPIN3 have a conserved function in shade response. Surprisingly, under the normal growth condition, mtpin1 mtpin3 displayed the constitutive shade avoidance responses, such as the elongated petiole, smaller leaf, and increased auxin and chlorophyll content. Therefore, MtPIN1 and MtPIN3 play dual roles in regulation of shadeavoidance response under different environments. Furthermore, these data suggest that PIN3,4,7 and its orthologs have evolved conserved and specific functions among species.